Evaluation of Bacillus subtilis, Pseudomonas aeruginosa and Pseudomonas fluorescens as biological control agent of Fusarium oxysporum f. sp. Cubense - Hassan, Iznee Rehanna (2016)
In Malaysia, bananas are the second most important fruit crop and ranked as the 29th top world producer. However, production and export has declined mainly due to disease caused by Fusarium oxysporum f. sp. cubense (Foc) especially on bananas of type Cavendish. The disease is known as Panama disease. Up to today, there is no definite solution towards Panama disease. Present methods are only able to delay the detrimental effect of Foc. The demand of organic food production by consumers is also increasing. These justifications lead to finding alternative method which is biological control. The objectives of this research were to determine the most effective bacterium as biological control agent of F. oxysporum f. sp. cubense and to identify presence of metabolites production of the bacteria that suppress Foc growth. Three different bacteria namely Pseudomonas fluorescens (UMB20), Pseudomonas aeruginosa (KMB25) and Bacillus subtilis (B40) strain were tested against Foc in PDA medium. The antagonistic metabolite production was evaluated using two different methods; double plate method and culture filtrate. The experimental design was completely randomized design and the treatment was replicated five times. Percentage inhibition of radial growth (PIRG), fungal radial growth and spore production were measured and enumerated for each treatment and compared to determine the most effective bacterium. The results from this experiment show that P. aeruginosa gave the highest PIRG of the Foc (27.86%) compared to the other two bacteria. B. subtilis and P. fluorescens gave PIRG of 9.274 and 26.01% respectively. The non-volatile metabolites showed more suppressive effect than volatile metabolites with PIRG of 76.53, 35.442 and 20.81% by P. aeruginosa, B. subtilis and P. fluorescens respectively.